Violence toward healthcare workers employed in Emergency Departments: A review of Italian regulations and international guidelines for the risk assessment and management - Francesco CHIRICO; Gabriella NUCERA; Angelo SACCO; Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: Workplace violence (WV) and harassment are emergent and harmful phenomena in healthcare settings, especially in Emergency Departments (EDs). This work aims to review scientific literature and European and Italian Regulations on WV perpetrated by third parties against healthcare workers (HCWs). Methods: This study employed a narrative review method. Our search was conducted between October and December 2021 in PubMed/Medline, CINHAL, and Google Scholar with several combinations of the following keywords: “emergency” (MeSH); “aggression”, “workplace violence”, “abuse”, “healthcare”, “third parties”, “threat”, “first aid”, in English and Italian. We also reviewed national, European, and international regulations and guidelines on this topic. Results and Discussion: Despite numerous studies in literature concerning WV against HCWs employed at EDs, especially nurses, this phenomenon is overlooked due to underreporting of WV. WV is a specific psychosocial risk factor different from lateral violence and work-related stress. For this reason, healthcare management should address this psychosocial risk factor with specific preventive measures. European employers should follow the EU-OSHA guidelines, while Italian employers should refer to Recommendation n.8 released by the Ministry of Health and other regional guidelines (e.g. those released in 2010 by the Emilia-Romagna region and in 2018 by Lazio region). Conclusion: WV against HCWs in EDs needs to be addressed timely. Specific risk assessment strategies and effective preventive and control measures can reduce the rate of WV-related injuries and the physical and psychological effects on HCWs. In addition, training and workplace health promotion programs can increase the well-being level among HCWs, productivity at work, and caregiver-patient relationships.